Political effects of employee participation - Sekerák, Marián (Teorija in praksa, 2014)
The notion of spillover thesis is known in many forms and is used in discussion of various concepts. This paper applies the thesis to the concept of employee participation and analyses its further and potential consequences for the wider political environment. There are internal discords in the discipline dealing with the real impact of employee participation and empirical evidence on it. Hence, we present a variety of attitudes to the issue. Advocates of the positive effects of the spillover thesis, such as Carole Pateman, support the idea of civic education, which has impact on political activism. Opponents criticizing this thesis point towards a multiplicity of determinants, which tend to modify the behaviour of a citizen. Multiple dimensions of social reality can act in the capacity of these determinants, such as various features of political culture, as well as the environment external to the political system. The authors of this paper do not aspire to propose a normative concept of the spillover thesis in workplace participation, however they wish to present a variety of approaches linked to this concept.
Keywords: Delavska participacija; Economic democracy; Ekonomska demokracija; participacija; Workers' participation; zaposleni